A high-sensitivity potentiometric 65-nm CMOS ISFET sensor for rapid E. coli screening - Jiang, Yu (2020)
Foodborne bacteria, inducing outbreaks of infection or poisoning, have posed great threats to food safety. Potentiometric sensors can identify bacteria levels in food by measuring medium's pH changes. However, most of these sensors face the limitation of low sensitivity and high cost. In this paper, we developed a high-sensitivity ion-sensitive field-effect transistor sensor. It is small sized, cost-efficient, and can be massively fabricated in a standard 65-nm complementary metal-oxide-semiconductor process. A subthreshold pH-to-time-to-voltage conversion scheme was proposed to improve the sensitivity. Furthermore, design parameters, such as chemical sensing area, transistor size, and discharging time, were optimized to enhance the performance. The intrinsic sensitivity of passivation membrane was calculated as 33.2 mV/pH. It was amplified to 123.8 mV/pH with a 0.01-pH resolution, which greatly exceeded 6.3 mV/pH observed in a traditional source-follower based readout structure. The sensing system was applied to Escherichia coli (E. coli) detection with densities ranging from 14 to 140 cfu/mL. Compared to the conventional direct plate counting method (24 h), more efficient sixfold smaller screening time (4 h) was achieved to differentiate samples' E. coli levels. The demonstrated portable, time-saving, and low-cost prescreen system has great potential for food safety detection.